Corporate governance and mergers & acquisitions in China: the role of internal capital markets and earnings management - Zhang, Hong (2017)
The objective of this thesis is to investigate the effect of corporate governance on M&A performance in China, particularly studying the role of internal capital markets (ICM) and earnings management (EM). (1) First, we re-evaluates the competing views of internal capital markets (ICMs). Using China’ Split-Share Structure Reform (SSSR) as a regulatory shock in the stock market, we study merger deals completed within a dominant form of ICMs in China – related-parties. We conduct a battery of difference-in-differences tests by employing 2200 M&A deals by Chinese bidders during the sample period of 2000 to 2014 and document a significant and positive treatment effect of the SSSR on related-party mergers and acquisitions (RPMA) compared to non-RPMAs measured by acquirers’ cumulative abnormal returns (CARs) around deal announcements. This treatment effect is particularly strong for deals undertaken by acquirers with low mutual fund ownership indicating benefits of the reform for weakly-governed firms. Our results are robust after controlling for possible propping by firm’s controlling shareholders among group-affiliated acquirers, alternate model specifications, and an array of control variables. Unlike prior findings, which generally hold a negative view of RPTs, our study reveals how major policy reforms in emerging markets setting can reduce abusive RPTs associated with managerial entrenchment and tunneling resulting in value gains through ICM transactions. (2) Second, we utilizes a sample of 1680 mergers by Chinese listed firms from 2000 to 2015 to examine the role of pre-merger earnings management in determining the method of merger payments and stock returns around the announcements of these key investment decisions. We document that income-increasing earnings management through both discretionary accruals and real activities in the year immediately preceding the mergers significantly increases the probability of deal payment in stock (or partially in stocks). Stock payment, although relatively much less frequent than pure cash payment, is associated with positive excess stock return around merger announcements in the short-run but negative excess returns in the long-run. This phenomenon is primarily due to pre-merger earnings management when acquires chose to pursue share-for-share deals. Our results reveal the capital market driven incentives for earnings management and indicate stock offers for privately held targets may reduce information asymmetric problems in mergers due to poor financial reporting quality of the listed acquirers in China.